Application of fingerprint identification for the smart academic calendar management system - Nguyen , Van Thai; Tran, Thu Ha; Le , Hoang Minh; Duong , Thi Cam Tu; Truong , Thi Bich Nga (Journal of Technical Education Science, 2016)
Currently, the tracking and monitoring student’s classroom participation are mostly done by lecturers before and/or after each lesson. In fact, this procedure had several inconveniences, such as time consuming, errors or confusion, etc... With a system scan and fingerprint identification is placed in front of the class, the student’s class attendance will be checked by themselves quickly and accurately. Developing completely a smart academic calendar management system consists of major functions such as: monitoring of lecturer’s teaching time; monitoring of student’s academic: attendance, tardiness, leaving early, absence, etc... The smart academic calendar management system consists of: 1) Developing a cloud computing software which used to monitor and manage both of student’s academic calendar and lecturer’s teaching time based on fingerprint’s student at in/out time of the class; 2) Designing a database used to store collected student’s fingerprint data from fingerprint scanners, which allows students, parents, lecturers, managers can access via internet browser. The system has been installed and operated experimentally within one year at the Faculty of High Quality Training (FHQ), Hochiminh City University of Technology and Education (HCMUTE) and has been get good results. This system may deploy widely for the entire university, other universities, colleges, etc...